Implementasi Digital Marketing Berbasis Website pada UMKM Kipas Banyu Biru untuk Mengembangkan Strategi Bisnis - Afraah , Sayyidah Maulidatul; Nugraheni, Diyah Dwi; Haryanto , Zelania In; Artanto , Brahmastya (Universitas Islam Indonesia, 2025)
This community service aims to develop the business strategy of Kipas Banyu Biru MSME through the implementation of website-based digital marketing. This MSME has experienced a decline in marketing due to limited use of technology, so digital transformation is needed to expand market reach and increase competitiveness. The methods used in the community service include the stages of data collection, website design and implementation, digital marketing system integration, digital advertising implementation, and performance analysis and evaluation. The website is designed to display product portfolios, business profiles, and direct communication features via WhatsApp Business. After implementation, the website is integrated with Google Analytics, Google Tag Manager, and Google Ads to support data-based digital marketing activities. Results showed 345 new users, 1,900 interactions, and 674 page views within a month. The ad campaign generated 249 clicks (CTR 2.29%) with a 1.61% conversion rate, though further improvement is needed. With this digital foundation, the MSME is better positioned to enhance its presence in local and global markets.